Na puti v Berlin . On the Way to Berlin - Ershov, Mikhail (Lenfilm, 1969)
The last days of the Second World War, the fight for Berlin. One part of the city after another is being captured by the Soviet army. The commandant of the city, Zaitsev, tries to solve everyday problems - from reviewing a music-hall program to arranging for the transportation of the elephant from the zoo. The film begins with extracts from Nazi newsreels and ends with footage of the signing of the capitulation.